Milky Way and Andromeda analogues from the TNG50 simulation - Pillepich, Annalisa; Sotillo-Ramos, Diego; Ramesh, Rahul; Nelson, Dylan; Engler, Christoph; Rodriguez-Gomez, Vicente; Fournier, Martin; Donnari, Martina; Springel, Volker; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2024)
We present the properties of Milky Way- and Andromeda-like (MW/M31-like) galaxies simulated within TNG50, the highest resolution run of the IllustrisTNG suite of lambda-cold dark matter magnetohydrodynamical simulations. We introduce our fiducial selection for MW/M31 analogues, which we propose for direct usage as well as for reference in future analyses. TNG50 contains 198 MW/M31 analogues, that is, galaxies with stellar discy morphology, with a stellar mass in the range of $M_* = 10^{10.5 - 11.2}~\rm {\rm M}_{\odot }$, and within an MW-like 500 kpc-scale environment at $z=0$. These are resolved with baryonic (dark matter) mass resolution of $8.5× 10^4\rm {\rm M}_{\odot }$ ($4.5× 10^5\rm {\rm M}_{\odot }$) and $\sim 150$ pc of average gas spatial resolution in the star-forming regions. The majority of TNG50 MW/M31 analogues at $z=0$ exhibit a bar, 60 per cent are star-forming, the sample includes three Local Group-like systems, and a number of galaxies host one or more satellites as massive as, for example, the Magellanic Clouds. Even within such a relatively narrow selection, TNG50 reveals a great diversity in galaxy and halo properties, as well as in past histories. Within the TNG50 sample, it is possible to identify several simulated galaxies whose integral and structural properties are consistent, one or more at a time, with those measured for the Galaxy and Andromeda. With this paper, we document and release a series of broadly applicable data products that build upon the IllustrisTNG public release and aim to facilitate easy access and analysis by public users. These include datacubes across snapshots
Online veröffentlicht: 18. September 2024
Gesehen am 25.05.2025